2022
DOI: 10.2147/ppa.s366083
|View full text |Cite
|
Sign up to set email alerts
|

Relation Among Anxiety, Depression, Sleep Quality and Health-Related Quality of Life Among Patients with Systemic Lupus Erythematosus: Path Analysis

Abstract: Purpose This study aimed to examine the relationship between anxiety, depression, sleep quality and health-related quality of life among systemic lupus erythematosus (SLE) patients in China. Patients and Methods After ethical approval and obtaining participants’ informed consent, a cross-sectional study was conducted in The First Affiliated Hospital of Anhui Medical University between October 1, 2021 and January 30, 2022. The data comprised demographic information, numb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 38 publications
(38 reference statements)
0
6
0
5
Order By: Relevance
“…The shortest has been diagnosed only six months before the research, the longest has been diagnosed for 33 years by J Pharm Sci Clin Res, 2023, 01 110 the clinician. This shown that SLE is a chronic disease, which stated in many studies (Chen et al, 2022). The demographic data of the respondents are shown in table 2.…”
Section: Resultsmentioning
confidence: 80%
See 2 more Smart Citations
“…The shortest has been diagnosed only six months before the research, the longest has been diagnosed for 33 years by J Pharm Sci Clin Res, 2023, 01 110 the clinician. This shown that SLE is a chronic disease, which stated in many studies (Chen et al, 2022). The demographic data of the respondents are shown in table 2.…”
Section: Resultsmentioning
confidence: 80%
“…In Brazil, the prevalence ranges from 20 to 150 cases per 100,000 persons with the most prevalence were reported, and it appears to be growth more and more. People of Black/African American or Asian origin have a higher risk for SLE than White/Caucasian individuals, and show more serious disease phenotypes (Chen et al, 2022;Carrasco et al, 2013). Some data in Indonesia are obtained from hospitalized patients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…29 The financial burden of treatment and regular followups for SLE patients is a significant expense for families, especially considering the low per capita monthly family income. 30 This increased financial pressure can further diminish the QOL of SLE patients. Employment status 31 is another factor impacting QOL, as working late shifts may similarly affect overall well-being.…”
Section: Discussionmentioning
confidence: 99%
“…The total score ranges from 0 to 21, with higher scores indicating poorer sleep quality. The PSQI demonstrated good validity and reliability among the Chinese patient population ( Chen et al, 2022 ).…”
Section: Methodsmentioning
confidence: 99%